Impact of Financial Literacy and Interest in Saving on Consumptive Behavior: Case Study of Students at SMK 1 Kotamobagu - Tamboto, Henry J.D.; Palangda, Listriyanti (PT. Riset Press International, 2025)
This study aims to determine the impact of financial literacy and interest in saving on the consumer behavior of students at SMKN Kotamobagu. Consumer behavior among adolescents is increasing with easy access to technology and information, so adequate financial understanding and motivation to save from an early age are needed. The research method used is quantitative with a survey approach. Data collection techniques were carried out by distributing questionnaires to 63 students selected as samples using purposive sampling techniques. Data were analyzed using multiple linear regression to determine the effect of financial literacy variables and interest in saving on consumer behavior. The results of the analysis show that both financial literacy and interest in saving simultaneously have a significant effect on student consumer behavior. Partially, financial literacy has a significant negative effect on consumer behavior, which means that the higher the level of financial literacy, the lower the level of student consumption. Interest in saving also has a significant negative effect, indicating that students with high interest in saving tend to control consumer urges better. These findings emphasize the importance of strengthening financial literacy education and habituation of saving among students as a preventive measure against unhealthy consumption patterns.